Cognitive Effects of Aromatase and Possible Role in Memory Disorders - Rosenfeld, Cheryl S.; Shay, Dusti A.; Vieira-Potter, Victoria J. (Frontiers in Endocrinology, 2018)
Diverse cognitive functions in many vertebrate species are influenced by local conversion of androgens to 17-estradiol (E2) by aromatase. This enzyme is highly expressed in various brain regions across species, with some inter-species variation in terms of regional brain expression. Since women with breast cancer and men and women with other disorders are often treated with aromatase inhibitors (AI), these populations might be especially vulnerable to cognitive deficits due to low neuroE2 synthesis. Animal models have been useful in deciphering aromatase effects on cognitive functions. Consequences of AI administration at various life cycle stages have been assessed on auditory, song processing, and spatial memory in birds and various aspects of cognition in rodent models. Additionally, cognitive deficits have been described in aromatase knockout (ArKO) mice that systemically lack this gene throughout their lifespan. This review will consider evidence to date that AI treatment in male and female rodent models, birds, and humans results in cognitive impairments. How brain aromatase regulates cognitive function throughout the lifespan, and gaps in current knowledge will be considered, along with future directions to better define how aromatase might guide learning and memory from early development through the geriatric period. Better understanding the importance of E2 synthesis on neurobehavioral responses at various ages will likely aid in the discovery of therapeutic strategies to prevent potential cognitive deficits, including Alzheimer’s Disease, in individuals treated with AI or those possessing CYP19 gene polymorphisms, as well as cognitive effects of normal aging that may be related to changes in brain aromatase activity.